Web Based Project Progress Monitoring for Construction Management: Pemantauan Kemajuan Proyek Berbasis Web untuk Manajemen Konstruksi - Muhammad Eko Mujahidin; Rohman Dijaya (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Project progress reporting is a critical component of construction management because project success is determined not only by completion time and final outcomes but also by continuous monitoring of work progress. Specific Background: PT. Albi Jaya Persada manages multiple construction projects, where project monitoring is constrained by distant project locations, delays in information delivery, difficulties in verifying field reports, and the accumulation of project documentation. Knowledge Gap: The existing monitoring process relied on manual reporting and communication methods that complicated verification, supervision, and decision-making activities. Aims: This study aimed to design and implement a web-based project progress monitoring system for PT. Albi Jaya Persada to support project supervision and reporting activities. Results: The developed system provides functionalities for project data management, sub-work monitoring, material tracking, progress documentation, complaint handling, and project supervision through dedicated interfaces for administrators, foremen, and directors. Black-box testing showed that all tested system functions operated according to the expected requirements and produced valid results. Novelty: The study introduces an integrated web-based monitoring platform that combines project progress reporting, material monitoring, documentation management, and communication of project constraints within a single system environment. Implications: The system supports directors in monitoring ongoing projects, reviewing project and material data, tracking work progress, and providing solutions to issues encountered during project execution.Highlights: Integrated platform supports project records, materials, documentation, and complaint management within one environment. Separate user interfaces were developed for administrators, foremen, and directors according to their responsibilities. Functional testing confirmed that all evaluated features operated as expected and produced valid outputs. Keywords: Web-Based Monitoring System; Project Progress Monitoring; Construction Project Management; Black Box Testing; Project Supervision